Catheter Ablation Versus Medical Therapy for Atrial Fibrillation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (September 2019) - Asad, Zain Ul Abideen; Yousif, Ali; Khan, Muhammad Shahzeb; Al-Khatib, Sana M.; Stavrakis, Stavros
Abstract : Background: Despite the publication of several randomized clinical trials comparing catheter ablation (CA) with medical therapy (MT) in patients with atrial fibrillation (AF), the superiority of one strategy over another is still questioned by many. In this meta-analysis of randomized controlled trials, we compared the efficacy and safety of CA with MT for AF. Methods: We systematically searched MEDLINE, EMBASE, and other online sources for randomized controlled trials of AF patients that compared CA with MT. The primary outcome was all-cause mortality. Secondary outcomes included cardiovascular hospitalizations and recurrence of atrial arrhythmia. Subgroup analyses stratified by the presence of heart failure with reduced ejection fraction, type of AF, age, and sex were performed. Risk ratios (RRs) with 95% CIs were calculated using a random effects model, and Mantel-Haenszel method was used to pool RR. Results: Eighteen randomized controlled trials comprising 4464 patients (CA, n=2286; MT, n=2178) were included. CA resulted in a significant reduction in all-cause mortality (RR, 0.69; 95% CI, 0.54–0.88; P =0.003) that was driven by patients with AF and heart failure with reduced ejection fraction (RR, 0.52; 95% CI, 0.35–0.76; P =0.0009). CA resulted in significantly fewer cardiovascular hospitalizations (hazard ratio, 0.56; 95% CI, 0.39–0.81; P =0.002) and fewer recurrences of atrial arrhythmias (RR, 0.42; 95% CI, 0.33–0.53; P <0.00001). Subgroup analyses suggested that younger patients (age, <65 years) and men derived more benefit from CA compared with MT. Conclusions: CA is associated with all-cause mortality benefit, that is driven by patients with AF and heart failure with reduced ejection fraction. CA reduces cardiovascular hospitalizations and recurrences of atrial arrhythmia for patients with AF. Younger patients and men appear to derive more benefit from CA. Abstract : Supplemental Digital Content is available in the text.